ANALYSIS OF HEALTH LEVEL OF BMT NURUL ISLAM BATAM BASED ON PERMENKOP NUMBER: 35.3/Per/M.KUKM/X/2007 YEAR 2017-2019 - Abdul Wachid (JURNAL AS-SAID, 2022)
This Research aimed to perceive about syaria micro finance institution health level specially in BMT Nurul Islam as the object. Analysis of BMT Nurul Islam Batam Health level research used the guidance which has been released by Cooperation Ministry number: 35.3/Per/M.KUKM/X/2007 about KJKS and UJKS health guidance. The aspect that be assesed on that guidance are, capital, earning asset quality, management, eficiency, liquidity, autonomy and growth, cooperation identity and also obedience to sharia principle periode that used on this research is 2017-2019. The research result of BMT K Health level on Nurul Islam periode 2017-2019 based on permenkop number: 35.3/Per/M.KUKM/X/2007 in aspect capitality, aktiva product quality, efficiency and liquidity is health.